Expected performance of the DEPFET sensor with signal compression: A large format X-ray imager with mega-frame readout capability for the European XFEL - Porro, Matteo; Andricek, L.; Bombelli, L.; De Vita, G.; Fiorini, C.; Fischer, Peter; Hansen, K.; Lechner, P.; Lutz, G.; Strüder, L.; Weidenspointner, G. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
The new DSSC (DEPFET sensor with signal compression) detector system is being developed in order to fulfil the requirements of the future XFEL in Hamburg. The instrument will be able to record X-ray images with a maximum frame rate of 5MHz and to achieve a high dynamic range. The system is based on a silicon pixel sensor with a new designed non-linear-DEPFET as a central amplifier structure. The detector chip is bump-bonded to mixed signal readout ASICs that provide full parallel readout and temporary data storage. The signals coming from the detector are processed by an analog filter, immediately digitized by 8-ENOB ADCs and locally stored in a custom designed memory. The ASICs are designed in 130nm CMOS technology. During the time gap of 99ms of the XFEL machine, the digital data are sent off the focal plane to a DAQ electronics that acts as an interface to the back-end of the whole instrument. The pixel sensor has been designed so as to combine high energy resolution at low signal charge with high dynamic range. This has been motivated by the desire to be able to be sensitive to single low energy photons and, at the same time, to measure at other positions of the detector signals corresponding to up to 104 photons of 1keV. In order to fit this dynamic range into a reasonable output signal swing, achieving at the same time single photon resolution, a strongly non-linear characteristic is required. The new proposed DEPFET provides the required dynamic range compression at the sensor level, considerably facilitating the task of the electronics. At the same time the DEPFET charge handling capacitance is enormously increased with respect to standard DEPFETs. The sensor matrix will comprise 1024×1024 pixels of hexagonal shape with a side-length of 136μm. The simultaneous implementation of the 5MHz frame rate, of the single low-energy photon resolution and of the high dynamic range goes beyond all the existing instruments and requires the development of new concepts and technologies.
Gesehen am 05.05.2023